2021
DOI: 10.3390/genes12040503
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Diversity of Cultivated and Wild Tomatoes with Varying Levels of Heat Tolerance

Abstract: Assessment of genetic variability in heat-tolerant tomato germplasm is a pre-requisite to improve yield and fruit quality under heat stress. We assessed the population structure and diversity in a panel of three Solanum pimpinellifolium (wild tomatoes) and 42 S. lycopersicum (cultivated tomatoes) lines and accessions with varying heat tolerance levels. The DArTseq marker was used for the sequencing and 5270 informative single nucleotide polymorphism (SNP) markers were retained for the genomic analysis. The ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 54 publications
(65 reference statements)
1
24
0
Order By: Relevance
“…The NCII analysis revealed that the hybrid combinations with the highest SCA effects for FS involved one parent (BJ01, CLN1621L, ATS020, and P005) (Ayenan et al, 2022; Ayenan, Danquah, Agre, et al, 2021; Ayenan, Danquah, Hanson, et al, 2021; Ro et al, 2021). Similarly, the hybrid combinations with the highest SCA estimates for NFP involved one of the following heat‐tolerant parents (CL5915‐93D4‐1‐0‐3, ATS020, BJ01, and CLN2026D) with high performance for NFP (Ayenan et al, 2022; Ayenan, Danquah, Agre, et al, 2021; Ayenan, Danquah, Hanson, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The NCII analysis revealed that the hybrid combinations with the highest SCA effects for FS involved one parent (BJ01, CLN1621L, ATS020, and P005) (Ayenan et al, 2022; Ayenan, Danquah, Agre, et al, 2021; Ayenan, Danquah, Hanson, et al, 2021; Ro et al, 2021). Similarly, the hybrid combinations with the highest SCA estimates for NFP involved one of the following heat‐tolerant parents (CL5915‐93D4‐1‐0‐3, ATS020, BJ01, and CLN2026D) with high performance for NFP (Ayenan et al, 2022; Ayenan, Danquah, Agre, et al, 2021; Ayenan, Danquah, Hanson, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These lines were obtained from the World Vegetable Center (WorldVeg), the University of Florida, and the Council for Scientific and Industrial Research ‐ Crops Research Institute (CSIR‐CRI) in Ghana. The lines were selected for their contrasting reaction to heat stress, their origins, and their genetic and phenotypic diversity (Ayenan et al, 2022; Ayenan, Danquah, Agre, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations